2018
DOI: 10.1016/j.atherosclerosis.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibition reduces atherosclerosis by enhancing lipoprotein clearance in Ldlr type 1 diabetic mice

Abstract: These data suggest that tighter glycemic control in diabetes can improve lipoprotein clearance exclusive of Ldlr, likely via HSPG and bile acid pathways, and has an overall net positive effect on atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 47 publications
6
44
2
1
Order By: Relevance
“…Similarly, STZ-treated mice fed the HFC diet exhibited a significant increase in the average necrotic core size (26.5 ± 1.9 vs 14.9 ± 2.2% of plaque size for STZ- vs control-treated mice that had been fed the HFC diet; Figures 3G – I ). This is consistent with observations that STZ-treatment increases high fat diet-induced atherosclerosis in other mouse models such as low density receptor-deficient mice ( Vikramadithyan et al, 2005 ; Johnson et al, 2011 ; Al-Sharea et al, 2018 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, STZ-treated mice fed the HFC diet exhibited a significant increase in the average necrotic core size (26.5 ± 1.9 vs 14.9 ± 2.2% of plaque size for STZ- vs control-treated mice that had been fed the HFC diet; Figures 3G – I ). This is consistent with observations that STZ-treatment increases high fat diet-induced atherosclerosis in other mouse models such as low density receptor-deficient mice ( Vikramadithyan et al, 2005 ; Johnson et al, 2011 ; Al-Sharea et al, 2018 ).…”
Section: Resultssupporting
confidence: 92%
“…In fact, children with type 1 diabetes exhibit increased aortic intima-media thickness, an early marker of subclinical atherosclerosis ( Harrington et al, 2010 ). Studies in animal models, such as atherosclerosis susceptible mice, have revealed that hyperglycemia is associated with increased aortic sinus atherosclerosis ( Park et al, 1998 ; Vikramadithyan et al, 2005 ; Werstuck et al, 2006 ; Johnson et al, 2011 ; Veerman et al, 2013 ; Venegas-Pino et al, 2013 ; Al-Sharea et al, 2018 ). However, the effects of hyperglycemia on coronary artery atherosclerosis are less well-studied, in part because conventional mouse atherosclerosis models, such as apolipoprotein E (apoE) or LDLR deficient mice, do not develop substantial coronary artery atherosclerosis or subsequent myocardial infarction ( Gonzalez et al, 2016 ; Trigatti and Fuller, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that SGLT2 inhibitors reduce the development of atherosclerotic lesions in diabetic and non-diabetic mice [13][14][15][16]. Our results were consistent with these studies.…”
Section: Discussionsupporting
confidence: 93%
“…However, the effect of SGLT2 inhibitors on lipid pro les is not consistent in animal studies. Several previous studies have shown that SGLT2 inhibitors can lower lipid levels [14,19,20], while others have not [21][22][23][24][25]. Our results showed that empagli ozin could reduce the levels of triglyceride, total cholesterol and LDL, while there was no signi cant difference in HDL between the two groups.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation